Trust and Brand Love in Special Interest Tourism - Wijaya, Nyoman Surya; Arianty, A. A. Ayu Arun Suwi; Suwintari, Gusti Ayu Eka; Sudiarta, Nyoman (Fakultas Ekonomi, Universitas Muslim Indonesia, 2024)
The purpose of this study is to find out the role of tourists' trust in adventure tourism destination, and brand love for Bali in influencing tourists' attitudes in deciding to make a return visit. This study uses a quantitative design based on positivism. The population is tourists who have carried out alternative tourism activities in an unlimited number. A sample of 120 was selected purposively, collected using a questionnaire. Descriptive analysis using SPSS, and inferential analysis using SEM with Smart PLS software. Based on the analysis, it was found that: 1) there was a positive and significant influence on attitudes, trust, and brand love on the intention to visit again, 2) a positive and significant influence was also obtained on attitudes towards trust; 3) Attitude also had a positive and significant effect on brand love; 4) Trust and brand love were able to significantly mediate the influence of attitude on the intention to revisit. This study only focused on Indonesian tourists so the results could not generalize the overall tourists. Theoretically, this contributes to the enrichment of marketing management, especially the Theory of Planned Behavior. The practical implications for alternative tourism managers are how to make activities very memorable, fun, able to increase tourist confidence, and the role of the Bali brand love is an attraction to increase the intention to visit again